2016
DOI: 10.1002/jat.3355
|View full text |Cite
|
Sign up to set email alerts
|

Molecular docking reveals the potential of phthalate esters to inhibit the enzymes of the glucocorticoid biosynthesis pathway

Abstract: Glucocorticoids (GCs) are well known to exert broad-based effects on metabolism, behavior and immunity. Their impaired synthesis and production lead to adverse health effects. Some environmental toxicants, including phthalate esters (PAEs), are associated with endocrine disruption. These endocrine-disrupting chemicals (EDCs) also cause adrenal toxicity and alteration of GC biosynthesis and their functions. Using in silico tools of Schrodinger Maestro 9.4, we performed a molecular docking study of 32 ligands in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 67 publications
0
21
0
Order By: Relevance
“…GC synthesis pathway is also a target. Different environmental toxicants, including phthalate esters together with bisphenols and their analogs pose deleterious effects on the biosynthesis of GC in vitro (Ahmad et al, 2017;Verma et al, 2018). These observations were confirmed in vivo using nitrate, a major anthropogenic contaminant in the FW environment.…”
Section: Corticosteroid Function Disruptionmentioning
confidence: 67%
“…GC synthesis pathway is also a target. Different environmental toxicants, including phthalate esters together with bisphenols and their analogs pose deleterious effects on the biosynthesis of GC in vitro (Ahmad et al, 2017;Verma et al, 2018). These observations were confirmed in vivo using nitrate, a major anthropogenic contaminant in the FW environment.…”
Section: Corticosteroid Function Disruptionmentioning
confidence: 67%
“…Phthalic acid esters in living organisms can induce an effect like estrogens; therefore, PAEs are among the group of Endocrine Disrupting Compounds (ECDs). Data from in silico experiments have shown that some PAEs cause harmful effects on mammalian and non-mammalian organisms (e.g., [5]). For example, dibutyl phthalate (DBP) and benzyl butyl phthalate (BBP) and their metabolites were shown to be indicative of hemolysis and eryptosis in human erythrocytes [6].…”
Section: Introductionmentioning
confidence: 99%
“…(3) the determination of selected phthalates in raw and treated sewage samples from an MWWTP supported by CWs; (4) an assessment of the uptake of PAEs by plants used in CWs; (5) an evaluation of the possibility of using hydroponic cultivations for the effective removal of PAEs in MWWTPs.…”
Section: Introductionmentioning
confidence: 99%
“…A number of researchers are involved in the assessment of deleterious effects of EDCs on the human physiological system . For such assessment, in silico tools have been proven to be of great worth . In the present study, the effect of dioxins and DLCs on PXR and CAR has been determined using an in silico study.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 For such assessment, in silico tools have been proven to be of great worth. 15,16 In the present study, the effect of dioxins and DLCs on PXR and CAR has been determined using an in silico study. Results obtained were compared with the known inhibitors of these receptors.…”
mentioning
confidence: 99%